2011
DOI: 10.1111/j.1365-2478.2011.00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Gravity field and tectonic features of Block L2 in the Lamu basin, Kenya

Abstract: A B S T R A C TA gravity survey on the scale of 1: 250 000 was carried out in Block L2 located in the Lamu basin of south-east Kenya in order to study tectonic features and find out favourable petroleum prospects in the block. This paper, through data processing and synthetic interpretation of the measured gravity data in the block, discusses characteristics of the gravity field and their geological implications, determines the fault system and the basement depth, analyses features of the main strata, divides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…In contrast, sediment thicknesses in the domain of the eastern basins are much larger, pointing also to larger porosity variations (due to differential states of compaction). Our model is consistent with the available information on porosity-controlled density increase in the Anza (Jose and Romanov, 2012) and Lamu basins (Yuan et al, 2012). Assuming an alternative scenario of a fully compacted sediment package in the eastern basins domain with a homogeneous bulk density of 2710 kg m −3 , for instance, would increase the gravity response locally by up to +80 mGal.…”
Section: Model Sensitivity and Robustnesssupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, sediment thicknesses in the domain of the eastern basins are much larger, pointing also to larger porosity variations (due to differential states of compaction). Our model is consistent with the available information on porosity-controlled density increase in the Anza (Jose and Romanov, 2012) and Lamu basins (Yuan et al, 2012). Assuming an alternative scenario of a fully compacted sediment package in the eastern basins domain with a homogeneous bulk density of 2710 kg m −3 , for instance, would increase the gravity response locally by up to +80 mGal.…”
Section: Model Sensitivity and Robustnesssupporting
confidence: 86%
“…Deposits of the Lamu Basin are lithologically described as a repetitive sequence of mainly siliciclastic rocks (sandstones, siltstones, shales) and intercalated limestones (Nyagah, 1995; Table 1). Direct evidence on the density configuration of the basin infill is provided by the study of Yuan et al (2012), who jointly investigated reflection seismic and gravity data from the central Lamu Basin. According to these observations, density increases with depth and age of the depositional sequences (the main ones of which are of Cenozoic, Cretaceous, Jurassic and Permian/Triassic ages).…”
Section: A1 Eastern Kenyamentioning
confidence: 99%
“…To understand the style of margin formation in the WSB, we draw together a combination of seismic, gravity, magnetic, and geological evidence. Coffin et al [1986] confirmed the existence of oceanic crust just offshore of the Kenya-Somalia border as far north and west as 42.058E 2.528S, but inboard of this within the Tanzania Coastal Basin and extending onshore within the Lamu Embayment, thin crust (<13 km thick) [Reeves et al, 1987] of an ambiguous nature is covered by thick sediments (up to 112 km, Yuan et al [2012] and references therein). Based on gravity and magnetic modeling, Reeves et al [1987] proposed that this crust is oceanic in nature, consistent with observations of necking zones (as defined by Tugend et al [2015]) onshore along the western edge of the Lamu Embayment from seismic refraction data, which suggest sharp crustal thinning from over 40 km to probably less than 15 km at this location [Prodehl et al, 1997].…”
Section: Plate Tectonic Modelmentioning
confidence: 73%
“…The Permo‐Carboniferous to Tertiary sedimentary section consists of a seaward thickening sedimentary wedge, including continental rift basin sandstones, fluviodeltaic sandstones, marine shales, and carbonates. The sedimentary section has a minimum onshore thickness of 3 km, reaches about 10 km in the coastal areas, and is up to 13 km thick in the offshore depocenter [ Nyagah, ; Yuan et al, ].…”
Section: Regional Geological Frameworkmentioning
confidence: 99%
“…The sedimentary section has a minimum onshore thickness of 3 km, reaches about 10 km in the coastal areas, and is up to 13 km thick in the offshore depocenter [Nyagah, 1995;Yuan et al, 2012].…”
Section: Stratigraphymentioning
confidence: 99%